A Comparative and Corelative Study On Body Composition and Motor Performance of 14 Years Old Boys of Four Different Altitudes of Darjeeling District - Gurung, Jyan Chandra; Banerjee, Krishna (Journal of Sports Research, 2014)
The purpose of the study was to find out the difference in Body composition (skinfolds) and motor performance of 14 years old boys of Darjeeling. The samples are school students. Researcher had taken 100 male students each from Sukhia Pokhari Higher Secondary School (Alt.-7200 ft.), Trunbull higher Secondary school (Alt.-6700 ft.), Jnanpith High school (Alt.-3000 ft.) and Kadamtala High School(Alt.-430 ft.). Researcher had measured height and weight as personal data measured skinfolds of triceps, biceps, subscapular, supra spinale, iliac creast and medial calf for body composition. 50 mt. dash, shuttle run, standing broad jump and sit ups were motor performance parameters. It has been observed that there were significant differences in medial calf skinfold thickness, agility and strength endurance.